A Praça Portugal como lugar: negociações de sentidos em encontros presenciais e mediados pelo computador - Marques, Ana Cesaltina Barbosa (2010)
This dissertation investigates the constitution of senses of place to the Portugal square, in Fortaleza, Ceará, considering the experiences of young local goers on Saturday nights in 2008 and 2009. The analysis of uses to that space and the meanings created from individual and collective experiences considered interactions between the square and a online community of social network website orkut, called Praça Portugal. The zone of interaction was delineated by a cut set for this research, but is also considered a sign of a new condition of experience of space. The meetings in the online community Praça Portugal extended the experience of being together of young people who frequented the square in addition to face to face meeting on Saturdays. Living together in cyberspace represented the possibility of shifting social relations from local contexts for relationships established in other parameters of space and time. Observing the relationship between the customers themselves and with the space of square, was possible to identify, in 2008 and 2009, different senses of place to the Portugal square which has been attributed since the early 2000s: space for experiencing the freedom of action and expression; of conduct of parallel trade or barter of symbolic goods; confrontation with the diversity of styles associated with the consumption of symbolic goods; and stronger ties of friendship. From the viewpoint of the subjects, was found different ways to experience the senses of place collectively shared. The association between traditional and new possibilities of social interaction became possible to evidence the importance of communication processes for the establishment of links between subjects and spaces, so to set up places.